Acoustic echo cancelation using a pseudo-linear regression and QR-decomposition - Harteneck, M.; Stewart, R.W. (1996 IEEE International Symposium on Circuits and Systems, 1996)
In this paper the problem of acoustic echo cancelation is addressed using an adaptive IIR filtering algorithm based on a QR decomposition and a pseudo-linear regression. The proposed algorithm yields a computational complexity of O(N/sup 2/) multiply-accumulates. In echo cancelation simulations it shows fast convergence in single talk and double talk periods, and proves to be stable if the near-end signal and received signal are correlated due to a far-end echo path.